Pengaruh DAR dan ROA terhadap NPL pada Bank BNI Tbk. Periode 2013-2023 - Jessica Amalia; Niwayan Julia Sanistira Kayla Anjani; Agus Supriatna (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This study aims to determine the effect of Debt to Total Asset and Return on Asset on Non Performing Loan at PT Bank Negara Indonesia Tbk both partially and simultaneously. The research method used by the author in preparing the journal is a quantitative method, namely conducting research that describes the company's financial condition expressed in numerical form. Data collection is done by taking secondary limits in the form of financial reports of PT Bank Negara Indonesia Tbk listed on the Indonesia Stock Exchange using reports in the form of balance sheets and profit and loss for the period 2013 to 2023. The data analysis technique used is the classical assumption test, multiple linear regression analysis, model feasibility test (correlation coefficient test, determination coefficient test and F test) and T hypothesis test using SPSS software versions 26 and 27. The results showed that Debt to Asset Ratio and Return on Asset simultaneously affect Non Performing Loan at Bank Negara Indonesia Tbk. Period 2013-2023, with a sig value. (0,001) < 0,05.